DESAIN BAHAN AJAR CETAK BERBASIS PRAKTIK KUALIFIKASI PROGRAM DIPLOMA PADA PERGURUAN TINGGI JARAK JAUH: Studi Kasus Desain Modul Berbasis Praktik Pada Prodi Diploma IV Kearsipan - Siti Samsiyah; Herwati Dwi Utami; Yanti Hermawati (Arsip Nasional Republik Indonesia, 2014)
Long Distance Learning has a unique system in its process, that is, the distance between the students and their lecturers. In order to master study materials, a media is required as a tool for students. Books materials or modules are primary tools for students learning. Furthermore, there are other learning materials for students such as printing materials in digital formats that contain audio-video, dry lab, interactive videos programs, TV and radio features. For universities, long distance learning for diploma program is quite difficult since the program requires students to master vocational skills that relate to the program study. The curriculum standard has to be 60% for practice and 40% for theories. Of course, this requires universities to push students to do practice more than learning theories. Similarly, the standard of Indonesian National Qualification Network (KKNI-Kerangka Kualifikasi Nasional Indonesia) expects students who graduate from Level 6 of Diploma IV shall have the capacity to arrange plans, innovations as well as evaluation of their own vocational skills. Modules of Active Records Management discuss on Records Management which is on the practice basis. From the research conducted, there are 9 (nine) modules of Active Records Management modules which are still not on the practice basis, they are modules 3,4,5,6,7,8,9. In order to design a module profile on the practice basis, the research mainly focuses on modules 6 and 9. This qualitative research is conducted with a combination of modules studies by records and archives experts to see the materials’ quality and practice competency. Moreover, instructional designers also review the modules for its learning designs. The research is expected to achieve high quality and appropriate modules to meet the requirement of diploma and distance learning programs. The objective of this research is to describe records management modules as one of the modules which are practice basis and to identify the level of understanding of diploma program students at long distance learning universities. The target is the construction of A Learning Model on Practice Basis for Diploma Program at Long Distance Universities.